2019
DOI: 10.1002/jbmr.3842
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Bone Fractures in Hemodialysis Patients Treated with Proton Pump Inhibitors in Real World: Results from the Dialysis Outcomes and Practice Patterns Study (DOPPS)

Abstract: Long‐term treatment with proton pump inhibitors (PPIs) is associated with an increased risk of fractures in the general population. PPIs are widely prescribed to dialysis patients but to date no study has specifically tested, by state‐of‐art statistical methods, the relationship between use of PPIs and fractures in this patient population. This study aimed to assess whether use of PPIs is associated with bone fractures (ie, hip fractures and fractures other than hip fractures) in a large international cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
1
13
0
5
Order By: Relevance
“…Recent data showed that both PPI and warfarin are associated with increased risk of fracture, cardiovascular disease, and mortality in dialysis patients [ 38 40 ]. PPI use is associated with mineral and vitamin deficiency, including magnesium, calcium, or vitamin B12, which contribute to bone health.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data showed that both PPI and warfarin are associated with increased risk of fracture, cardiovascular disease, and mortality in dialysis patients [ 38 40 ]. PPI use is associated with mineral and vitamin deficiency, including magnesium, calcium, or vitamin B12, which contribute to bone health.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, proton pump inhibitors (PPI) have been linked to fractures and in Australia their use has increased by greater than 1000% from 1995 to 2006 . Fusaro et al found in a large study of 27 097 haemodialysis patients that almost half were on a PPI regimen and their use was associated with significantly higher rates of bone and hip fractures . Warfarin use is also common amongst CKD and HD patients and has similarly been linked with fractures .…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that PPI use increases the risk of osteoporotic fracture in elderly people aged > 65 years [20]. It has also been reported that PPI is associated with fractures in hemodialysis patients at high risk of fracture [24]. Most of the studies reported the existence of an association between PPI use and osteoporotic fracture risk.…”
Section: Interpretation and Comparison With Other Studiesmentioning
confidence: 99%
“…Prior studies that reported that PPIs are associated with osteoporotic fractures yielded inconsistent results on the duration and use patterns of PPIs, which influence the osteoporotic fracture risk. Most studies have reported that any use [15][16][17][18][19][20][21][22][23][24] or current use [25][26][27] of PPIs increases the osteoporotic fracture risk. However, the association between the duration of PPI use and osteoporotic fracture has been inconsistently reported, with some studies showing a relation [21] and others reporting no relation [27,28].…”
Section: Introductionmentioning
confidence: 99%